Processes and methods for selecting system-wide parameters and analysis of resistance against third-party channel attacks for the key encapsulation mechanism DSTU 8961:2019 - Kulibaba , V.A. (Radiotekhnika, 2021)
In recent years, there has been significant progress in the creation of quantum computers. If scalable quantum computers are implemented in the near future, this will jeopardize the security of the most widely used public key cryptosystems. The most vulnerable are public-key schemes based on factorization, discrete logarithms and elliptic curve cryptography. Currently, the main task is to develop, evaluate, study and standardize asymmetric crypto transformations at the international level, including mechanisms of key encapsulation and directional encryption, resistant to attacks by violators of the post-quantum period. An important feature of the transition and post-quantum period is the usage of new mathematical methods to opposite quantum crypto analysis. The paper considers the main attacks on the mechanisms of key encapsulation and directional encryption, as well as system-wide parameters of the DSTU 8961: 2019 standard, which affect the resistance to attacks and the complexity of transformations. Methods for generating system-wide parameters of 5 and 7 levels of stability – 512 bits of classical and 256 bits of quantum security, as well as the protection of the algorithm from attacks by third-party channels are considered. The dependence of encryption and decryption time on the level of stability is analyzed. The results of calculations of system-wide parameters for stability levels 256/128, 384/192 and 512/256 are presented, as well as recommendations for the selection of system-wide parameters depending on the environment and computing capabilities. Sets of parameters selected and recommended for use in the DSTU 8961: 2019 standard are given. Conclusions are drawn about the possibility of applying the DSTU 8961 standard in the post-quantum period.